DC's legends of tomorrow. The complete fourth season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (Warner Bros. Entertainment, 2019)
After defeating the demon Mallus by cuddling him to death, the Legends join John Constantine and Ava Sharpe's Time Bureau to save their world, and their legacy, from magical creatures from myths, fairytales, and legends who have infected history. As the Legends time-travel across historical events and encounter famous figures, they now have an added shot of magical craziness.